Triangulation of Subjectivity - Wolfgang Fichten; Birgit Dreier (Forum: Qualitative Social Research, 2003)
The Oldenburger action research in which praxis-orientated school projects are carried out by research teams consisting of teachers and students grants exceptional discovery and reflection opportunities. This particular research practice is framed by social-constructive hypotheses. On the basis of these hypotheses, a unified correlation of the understanding of the object, methodology and perspectivity can be generated. When connecting the triangulation of methods with the triangulation of subjectivity, research seems to be a continuous perspective process. The foundation of a triangulation of subjectivity is to accentuate and to reflect on subjectivity. The examples taken from the "Forschungswerkstatt" show how different subjective accesses to the object of research can be worked on in a constructive way and used as a quality-increasing element in research. In the course of data interpretation and process reflection the multiperspectivity which arises from the team setting generates different approaches concerning the reading, differentiation and explanations. These new approaches can then be integrated into the perspective construction of the subjects. Restructuring and modification of subjective perspectives are the results of a self-referential orientated action research, which can be integrated into a "community of practice." URN: urn:nbn:de:0114-fqs0302293